Foreign economic policy coordination in CARICOM : the case of the GSTP. - Henry, Andre-Vincent (1992)
Discusses the failure of CARICOM and its member states to approach the Global System of Trade Preferences (GSTP) as a single entity. Attempts to determine whether the internal structures of CARICOM are adequate to fulfil the requirements of the CARICOM Treaty on the coordination of foreign economic policy.